Reform and the papacy in the eleventh century : spirituality and social change - Cushing, Kathleen G. (Manchester medieval studies., 2020)
"This book explores the relationship between the papacy and reform against the backdrop of social and religious change in later tenth and eleventh-century Europe. Placing this relationship in the context of the debate about 'transformation', it reverses the recent trend among historians to emphasise the reform developments in the localities at the expense of those being undertaken in Rome. It focuses on how the papacy took an increasingly active part in shaping the direction of both its own reform and that of society, whose reform became an essential part of realising its objective of a free and independent Church. It also addresses the role of the Latin Church in western Europe around the year 1000, the historiography of reform, the significance of the 'Peace of God' as a reformist movement, the development of the papacy in the eleventh century, the changing attitudes towards simony, clerical marriage and lay investiture, reformist rhetoric aimed at the clergy, and how reformist writings sought to change the behaviour and expectations of the aristocracy. Summarising current literature while presenting a cogent and nuanced argument about the complex nature and development of reform, this book will be invaluable for an undergraduate and specialist audience alike." --Back cover.